Hans Jonas' Concept of "Responsible Ethics" And the Mental Features of Traditional Ethical Theory - Samandarova Mukarram Borievna (Scientific Trends, 2025)
The article systematically examines the issues of traditional moral theory and its impact on social life, analyzes the concepts of the ethics of responsibility, and the specific aspects of Hans Jonas's concept of moral theory, as well as his fundamental work, "The Principle of Responsibility: The Experience of Morality in the Conditions of Technological Civilization."
Keywords: Ethics of responsibility, traditional, humanity, technological civilization, man, nature, social-ethical obligation, theory, future.